Neo-Victorian Transcorporeality: Narrating Julia Pastrana's Body. - Pettersson, Lin Elinor (Universitat Jaume I, 2023)
Julia Pastrana (1834-1860) features prominently in neo-Victorian biofiction, which is probably indebted to her tragic life and posthumous exploitation in the hands of her husband-manager Theodore Lent. Pastrana’s career surpassed her death when Lent continued touring her embalmed body – an exhibition that would outlive him into the late twentieth century. Although Pastrana was repatriated and buried in 2013, she did not reach the final rest as her story continues to fascinate twentieth-first century audiences. This essay focuses on the ways in which Pastrana’s body has been constructed and produced narratively building on multiple discourses that straddle different disciplines and cultural settings that span three centuries. The two biofictional novels Julia Pastrana (2007) by Sandy Olson and Julian Fenech, and The Orphans of the Carnival (2016) by Carol Birch will be analysed through the lens of trans- corporeality (Alaimo, 2010). By drawing on twenty-first century feminist theory on the body that has placed emphasis on the body as a dynamic and travelling concept through its orientations and intersectionality, my principal aim is to provide new insights into the ways in which contemporary novelists have rendered Pastrana’s body.
Transcorporalidad neovictoriana: Narrando el cuerpo de Julia Pastrana
Keywords: Mujeres - S. XIX - En la literatura; Literatura inglesa - S. XXI; Trans-corporeality; Julia Pastrana; Neo-Victorianism; Biofiction; Freakery; Freak Shows; Stacy Alaimo; Orphans of the Carnival